Enhancement of biodiesel production from the green microalga Micractinium reisseri via optimization of cultivation regimes. Issue 1 (1st January 2020) - El-Sheekh, Mostafa M.; El-Mohsnawy, Eithar; Mabrouk, Mona E. M.; Zoheir, Wafaa F.
Abstract : The present work introduces a new strategy for enhancing a sustainable biodiesel from Micractinium reisseri by combining mixotrophic nutrition with nutrients stresses. Cultivating of Micractinium reisseri in 25 mg/l promoted lipid yield reaching 206%. While mixotrophic nutrition by 0.1 M glycerol promoted dry weight by 2.8 folds, 0.05 M glycerol enhanced lipid yield by 26% only. However, supplementation algal culture by 1 g/l sugarcane molasses promoted lipid content by 61% and total lipid yield by 31%. While polyunsaturated fatty acids (PUSFA) reduced from 48% to 31%, monounsaturated fatty acids (MUSFA) increased from 14% to 30% and Oleic and Stearic acids increased by 383% and 284%, respectively under optimized conditions. Evaluation of the produced biodiesel by monetarystandard EN 14214 and ASTM D-6751 analysis exhibited high-quality products. Combining mixotrophic nutrition with salts and nitrogen stresses led to encouragement switching the metabolic pathways towards lipid output that used as a biodiesel source.